2011
DOI: 10.1093/ecam/nen056
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum triquetrifolium—Derived Factors Downregulate the Production Levels of LPS‐Induced Nitric Oxide and Tumor Necrosis Factor‐α in THP‐1 Cells

Abstract: Based on knowledge from traditional Arab herbal medicine, this in vitro study aims to examine the anti-inflammatory mechanism of Hypericum triquetrifolium by measuring the expression and release of pro-inflammatory cytokines, tumor necrosis factor-α (TNF-α) and interleukine-6 (IL-6), and inducible nitric oxide synthase (iNOS) in human monocytic cells, THP-1. The effects were assessed by measuring the levels of secretory proteins and mRNA of TNF-α and IL-6, the levels of nitric oxide (NO) secretion and the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Several studies have revealed that natural products exhibit an extensive spectrum of biological activities such as, stimulation of the immune system, antibacterial, antiviral, anti-hepatotoxic, anti-ulcer, anti-inflammatory, antioxidant, anti-mutagenic, and anti-cancer effects [6,36,66,[84][85][86]. A variety of grains, cereals, nuts, soy products, olives, beverages such as tea and coffee, and spices including turmeric, garlic, ginger, black pepper, cumin and caraway confer a protective effect against cancer [33,35,36,66,85,87].…”
Section: The Wisdom Of the Past Led To The Discovery Of Chemopreventimentioning
confidence: 99%
“…Several studies have revealed that natural products exhibit an extensive spectrum of biological activities such as, stimulation of the immune system, antibacterial, antiviral, anti-hepatotoxic, anti-ulcer, anti-inflammatory, antioxidant, anti-mutagenic, and anti-cancer effects [6,36,66,[84][85][86]. A variety of grains, cereals, nuts, soy products, olives, beverages such as tea and coffee, and spices including turmeric, garlic, ginger, black pepper, cumin and caraway confer a protective effect against cancer [33,35,36,66,85,87].…”
Section: The Wisdom Of the Past Led To The Discovery Of Chemopreventimentioning
confidence: 99%
“…Even though a number of studies have been conducted to understand the mechanism of HP treatment on various disease conditions (Albert et al, 2002;Tedeschi et al, 2003;De Paola et al, 2005;Genovese et al, 2006a,b;Hammer et al, 2007;Saad et al, 2008;Dost et al, 2009;Cirak et al, 2010;Kraus et al, 2010;Samadi et al, 2010) only a few of them have reported the effect of HP on contractility of vascular system (Melzer et al, 1991;Apaydin et al, 2001;Gilani et al, 2005;Khan et al, 2009Khan et al, , 2010, however, there are no scientific reports with HP detailing its modulatory effects on the vascular tone. Hence, this study has investigated the vascular effects of HP at both smooth muscle and endothelial level.…”
Section: Discussionmentioning
confidence: 99%
“…Another origin of NO is iNOS which is responsible for the detrimental effect of NO in the inflammatory process. Previous researchers have described the inhibition of iNOS by HP (Tedeschi et al, 2003;Saad et al, 2008;Kraus et al, 2010). Endothelial cell xantine oxidase forms ROS (Villar et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that natural products exhibit an extensive spectrum of biological activities such as, stimulation of the immune system, antibacterial, antiviral, anti-hepatotoxic, anti-ulcer, anti-inflammatory, antioxidant, antimutagenic, and anti-cancer effects. [11][12][13][14][15] In addition, a number of medicinal plants and herbs have also been reported to reduce the risk of cancer in multiple sites. [16][17] Many commonly These Unani medicinal herbs may be valuable for optimizing the conventional anticancer therapy; and they can be used in combination with conventional anticancer drugs as a supportive therapy to improve health-related quality of life (HRQoL) of cancer patients.…”
Section: Use Of Unani Medicine As a Substitute To Conventional Chemotmentioning
confidence: 99%